2018
DOI: 10.2196/humanfactors.8017
|View full text |Cite
|
Sign up to set email alerts
|

VA FitHeart, a Mobile App for Cardiac Rehabilitation: Usability Study

Abstract: BackgroundCardiac rehabilitation (CR) improves outcomes for patients with ischemic heart disease or heart failure but is underused. New strategies to improve access to and engagement in CR are needed. There is considerable interest in technology-facilitated home CR. However, little is known about patient acceptance and use of mobile technology for CR.ObjectiveThe aim of this study was to develop a mobile app for technology-facilitated home CR and seek to determine its usability.MethodsWe recruited patients eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 48 publications
1
57
0
1
Order By: Relevance
“…A recent study by Beatty et al [50] illustrates the mixed methods process as they collected both quantitative and qualitative data to determine the usability of a mobile app for technology-facilitated home cardiac rehabilitation. Quantitative data included the SUS and task completion rate, whereas the qualitative data included questions about the functionality of the mobile app [50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Beatty et al [50] illustrates the mixed methods process as they collected both quantitative and qualitative data to determine the usability of a mobile app for technology-facilitated home cardiac rehabilitation. Quantitative data included the SUS and task completion rate, whereas the qualitative data included questions about the functionality of the mobile app [50].…”
Section: Methodsmentioning
confidence: 99%
“…The latter 2 columns include the quantitative data, for example, scales or items, and the qualitative data, for example, qualitative questions or observation types. For example, Beatty et al [50,58] used matching by integrating the task completion time (quantitative) with asking “I noticed that the _____ feature took you longer than some of the others. Tell me more about that?” (qualitative).…”
Section: Methodsmentioning
confidence: 99%
“…10 Mobile health (mHealth) applications proved useful to provide assistance in self-management, 11 symptom monitoring, 12 and home-based cardiac rehabilitation. 13 In addition, smart devices have the potential to generate new patient-reported outcome measures (PROMs) in HF patients. Their integrated sensor technologies allow not only for ambulatory data acquisition but also for more continuous monitoring of physiological data like heart rate or walking activity in the context of everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Third, mobile applications provide opportunities to share the data with the health care providers which has the potential to promote CR through subjective norms and social influence [32]. It has been reported that many patients had expected to share the obtained data with their health care providers and they viewed this as a key benefit of using mobile applications [33]. Another study has reported great promotion of participation in CR through interaction, communication and feedback [34].…”
Section: Discussionmentioning
confidence: 99%